Menjawab Persoalan tentang Imam Besar Abyatar dalam Markus 2:26: Sebuah Kritik Teks - Pujianto Hardjosanjoto; Bakhoh Jatmiko (SANCTUM DOMINE: JURNAL TEOLOGI, 2020)
ABSTRACT Mark 2:26 is one of the most disputed texts. The text's pivotal problem is around the accuracy between Jesus' narration and the historical facts in the Old Testament (1 Sam. 21:1-6). This discrepancy implies the authority of Christology and Bibliology in the Christian faith. This research was conducted to examine the text in order to answer the disputes around the text. The authors used a qualitative descriptive research method in this research with a textual criticism approach. The research approaches covered textual history, text's authorship history, and text's grammatical analysis. This research found that there were neither textual errors nor Jesus's mistakes in quoting a history. Addressing Abiathar as high priest is a part of the patristic culture in the priesthood tradition in Israel. Jesus’ motive in mentioning Abiathar closely related to the unfaithful story that has made him disposed as a high priest. Thus, the authority of Christ and the Bible as God's Word could not be overthrown by this passage. Keywords : Abiathar; High Priest; Mark 2:26